2020
DOI: 10.1080/02656736.2020.1843719
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy versus radiofrequency ablation for hepatocellular carcinoma: a systematic review and meta-analysis

Abstract: Purpose: To compare the efficacy and safety of stereotactic body radiotherapy (SBRT) with radiofrequency ablation (RFA) for hepatocellular carcinoma (HCC). Materials and methods: PubMed, MedLine, EMBASE, the Cochrane Library and Web of Science were searched to identify potentially eligible studies comparing the efficacy and safety of SBRT with RFA for HCC from January 1990 to May 2020. Hazard ratios (HRs) or odds ratios (ORs) with 95% confidence intervals (CIs) were used to determine the effect size for overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“… 48 On the contrary, Wang et al in a review and meta-analysis of 7928 patients, reported better local control of HCC with SBRT than with RFA especially for slightly larger tumors (> 2cm) with equivalent overall survival outcomes and comparable toxicity. 49 In addition, a large multi-institutional retrospective study by Kim et al including 2064 patients reported significantly lower local recurrence rates with SBRT than with RFA in both the unmatched and propensity score matched cohorts. 50 SBRT was also associated with superior local control in small tumors ≤ 3 cm irrespective of location, large tumors in subphrenic location and those that progressed after TACE.…”
Section: Comparison Of Sbrt With Other Techniquesmentioning
confidence: 98%
“… 48 On the contrary, Wang et al in a review and meta-analysis of 7928 patients, reported better local control of HCC with SBRT than with RFA especially for slightly larger tumors (> 2cm) with equivalent overall survival outcomes and comparable toxicity. 49 In addition, a large multi-institutional retrospective study by Kim et al including 2064 patients reported significantly lower local recurrence rates with SBRT than with RFA in both the unmatched and propensity score matched cohorts. 50 SBRT was also associated with superior local control in small tumors ≤ 3 cm irrespective of location, large tumors in subphrenic location and those that progressed after TACE.…”
Section: Comparison Of Sbrt With Other Techniquesmentioning
confidence: 98%
“…Three recent meta-analyses have aimed to provide objectivity to inform decision making. [68] , [69] , [70] The meta-analysis by Pan et al. included 10 studies comparing SBRT with RFA in patients with treatment-naïve HCC and showed superior 1- and 3-year local control with SBRT.…”
Section: Evidence and Indications For Sbrt In Hccmentioning
confidence: 99%
“…At present, three-dimensional conformal radiotherapy is the most widely reported external radiotherapy technique with relatively clear curative efficacy. High-level evidence has recently suggested the value of proton beam radiotherapy 60 and stereotactic radiotherapy 61 in the treatment of small HCC, and positive results of these two methods in PVTT are expected.…”
Section: Treatments For Hcc With Pvttmentioning
confidence: 99%